In vitro biocontrol potential of natural substance combination against plant pathogens - Somsri, A.; Saelao, P.; Thongsen, N.; Kenkhunthot, T.; Pilasombut, K.; Urairong, H.; Rumjuankiat, K. (International Journal of Agricultural Technology, 2025)
The antimicrobial potential of chitosan (CHT), banana peel vinegar (BPV) and plant-derived extracts from basil leaves (BE), fingerroot (FRE), and mangosteen peel (MSE) was evaluated against Diaporthe phaseolorum, Colletotrichum gloeosporioides, Fusarium oxysporum, Curvularia sp., and Xanthomonas campestris pv. campestris (Xcc). Among these, MSE and FRE exhibited the highest efficacy, with minimum inhibitory concentrations (MIC) of 0.006 mg/ml and 0.048 mg/ml, respectively. Both extracts also inhibited Xcc, showing partial synergistic effects with a fractional inhibitory concentration index (FICI) of 0.625. These results highlight the antimicrobial potential of natural compounds, offering valuable insights for developing sustainable strategies in plant disease management and biofungicide formulation.